Measurement of Usability and Adoption Rate in Academic Information Systems - Jufrike Kamu, Charly Himpong, Ralph Pascoal, (International Journal of Information Technology and Education, 2022)
E-learning is widely used as a learning medium that utilizes computer technology, computer networks or the Internet. Indonesia is the 8th country for e-learning users based on the total e-learning market each year, which is 25%. Student. The purpose of this research is to make the system more effective and efficient so that many students find it easy to collect data and re-register at SIA UNIMA, provide solutions to make SIA into an integrated system and an appropriate design in the UNIMA Campus Academic Information System. The method used to determine the level of acceptance of the Academic information system used at UNIMA can be analyzed using the TAM model. The results of this study indicate that the majority of students have been able to use e-learning well and will continue to use it in the future. The results of this study recommend that the learning process is better using e-learning so that the learning process becomes more effective.